miR-927 regulates insect wing development by targeting the Hippo pathway. - Yu, X.; Sun, B.; Gao, X.; Liu, Q.; Zhou, Z.; Zhao, Y. (Insect Science, 2025)
How organ size is determined is a fundamental question in life sciences. Recent studies have highlighted the importance of the Hippo pathway in regulating organ size. This pathway controls cell proliferation and cell death to maintain the proper number of cells. The activity of the Hippo pathway is tightly fine-tuned through various post-translational modifications, such as phosphorylation and ubiquitination. Here, we discover that miR-927 is a novel regulator of wing size. Overexpression of miR-927 decreases wing size, which can be rescued by co-expressing miR-927-sponge. Next, we show that miR-927 stimulates apoptosis and suppresses the expression of Drosophila inhibitor of apoptosis protein 1, a well-known target gene of the Hippo pathway. Genetic epistatic analyses position miR-927 upstream of Yorkie (Yki) to modulate the Hippo pathway. In addition, there is a matching miR-927 seed site in the yki 3' untranslated region (3'-UTR), and we demonstrate that yki 3'-UTR is the direct target of miR-927. Ultimately, our study reveals that the targeting of yki by miR-927 to regulate the Hippo pathway is conserved in Helicoverpa armigera. Administration of miR-927 via star polycation (SPc) nanocarrier effectively inhibits wing development in H. armigera. Taken together, our findings uncover a novel mechanism by which Yki is silenced at the post-transcriptional level by miR-927, and provide a new perspective on pest management.